Effects of various logistics packaging on the quality and microbial variation of bigeye tuna (Thunnus obesus) - Cheng, Zhizhen; Pan, Weicong; Xian, Wendong; Yu, Jin; Weng, Xudong; Benjakul, Soottawat; Guidi, Alessandra; Ying, Xiaoguo; Deng, Shanggui (Frontiers in Nutrition, 2022)
Bigeye tuna (Thunnus obesus) is an economically valuable ocean fish species. It is susceptible to contamination during storage and transportation; maintaining a healthy environment during transportation is critical to prevent quality deterioration. However, the influence of packaging on retaining freshness in transportation engineering remains unknown. Here, the impact of different transportation packaging on the quality and microbiological variation of bigeye tuna during logistics process was investigated. The aluminum foil paper (AFP) group had minimum temperature fluctuation during transportation and exhibited preferable water retaining capacity and color protection effect. AFP transport packaging efficiently prevented total volatile basic nitrogen content (TVB-N) creation and microbial growth. After 40 h, the TVB-N was 21.28 mg/100 g and microbial total plate count was 3.53 log10 CFU/g, which were within the acceptable range. Temperature fluctuations and packaging materials used during transportation had a major effect on the microbial community structure of bigeye tuna—Chitinophagaceae, Acinetobacter and Knoellia were dominant in the AFP group, while Pseudomonas, Acinetobacter, and Macrococcus were dominant in the expanded polystyrene foam and European logistics groups. The AFP box transport packaging limited Pseudomonas to a risk-free extent. AFP packaging may effectively restrain the growth of microorganisms from spoiling the freshness and preserve the quality of bigeye tuna. This study provided insights into understanding the effects of packaging material on maintaining quality during logistics transportation.